The Role of a Notary in the Establishment and Registration of a Limited Liability Company after the New AHU Online and Risk-Based OSS Systems Come into force - Danianto, Iswar; Bawono, Bambang Tri (Jurnal Konstatering, 2022)
This study aims to analyze proles, obstacles that arise and solutions that can be carried out as well as legal responsibilities of Notaries in the establishment and registration of Limited Liability Companies after the implementation of the new system AHU Online and Risk-Based OSS. This study uses an empirical juridical approach. The data used are primary and secondary data which are analyzed using descriptive qualitative methods. Based on the results of the study it was concluded that: 1)The notary still has a role in the establishment and legalization of the capital partnership company due to statutory orders.But for individual companies, nthe notary is not obliged to register it unless the notary is authorized by the client, then the notary becomes civilly responsible for this power of attorney. Notaries also do not have an absolute role in registering business licenses for companies according to Government Regulation Number 5 of 2021. However, notaries are often given the power to work on business licensing registration on Risk-Based OSS, so the notary is also liable civilly for this power of attorney. 2)Obstacles faced by a notary in the process of establishing and registering a limited liability company consist of internal constraints, namelyconstraints on the weak quality of human resources including the notary concerned. Notaries must continue to study, coordinate with various competent parties and attend legal seminars.then kexternal obstacles, namely obstacles that arise from the client, the AHU Online system and OSS as well as from other parties that are the cause. 3) The responsibility of a notary in the event of an error in the establishment and registration of a limited liability company is based on an error. Notaries can be held liable in civil, criminal, as well as based on the UUJN and the Code of Ethics on the deed he made.Meanwhile, the responsibility of a notary as a recipient of power of attorney in carrying out responsibilities which are essentially not his authority is a form of civil liability, not as a notary who is normative by referring to the provisions of Article 1365 of the Civil Code.Keywords: Company; Online; Submissions.